Legal Aid by the State as a Constitutional Right of the Poor: Problems and Challenges in Indonesia - Wibowo, Ari; Bangun, Michael Hagana (The Indonesian Journal of International Clinical Legal Education, 2021)
The provision of legal aid is one way to realize access to law and justice for the poor people provided by the state on the mandate of the constitution. Several regulations regarding legal aid have been issued by the state through the Act and its implementing regulations as well as from the Supreme Court or the Constitutional Court through the Supreme Court Regulations and the Constitutional Court's decisions. Legal aid is the constitutional right of every citizen to guarantee legal protection and guarantee equality before the law stipulated in Law Number 16 of 2011, the State is responsible for recognizing and protecting the human rights of every individual without differing backgrounds so that everyone has the right to be treated equally before the law is contained in Article 28D of the 1945 Constitution of the Republic of Indonesia. For the poor who experience legal problems in the form of injustice, they can request legal assistance from legal aid institutions that are regulated in legislation. The purpose of providing legal aid is to guarantee and fulfill the right for Legal Aid Recipients to gain access to justice, to realize the constitutional rights of all citizens in accordance with the principle of equality in law, to ensure the certainty that the implementation of Legal Aid is carried out equally across the territory of the Republic of Indonesia. , and to create an effective, efficient and accountable court.